1985
DOI: 10.1056/nejm198510033131403
|View full text |Cite
|
Sign up to set email alerts
|

Public Health Service Study on Reye’s Syndrome and Medications

Abstract: Between February and May 1984, we conducted a pilot study to examine the methods for a larger study of a previously reported relation between Reye's syndrome and medications. Thirty patients with Reye's syndrome, whose diagnosis was confirmed by an expert panel, and 145 controls were matched for age, race (black or not black), and antecedent illness (respiratory infection, chickenpox, or diarrhea) and selected from the same hospital, emergency room, or school, or identified by random digit dialing. Significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
34
0

Year Published

1986
1986
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(37 citation statements)
references
References 7 publications
1
34
0
Order By: Relevance
“…Several studies have indicated that the development of RS is linked to ASA therapy (24)(25)(26). Because of the possible inductive action of ASA on the whydroxylation system and the observation that DCAs in the serum of RS patients are mitochondrial inhibitors, ASA was administered to rats to determine its effect on the fatty acid whydroxylation system and in the formation of the DCAs using the 12-carbon atom fatty acid, LA, as substrate.…”
mentioning
confidence: 99%
“…Several studies have indicated that the development of RS is linked to ASA therapy (24)(25)(26). Because of the possible inductive action of ASA on the whydroxylation system and the observation that DCAs in the serum of RS patients are mitochondrial inhibitors, ASA was administered to rats to determine its effect on the fatty acid whydroxylation system and in the formation of the DCAs using the 12-carbon atom fatty acid, LA, as substrate.…”
mentioning
confidence: 99%
“…27 Efforts to raise awareness of the link between aspirin and RS included journal publications; warning statements in 1982 by CDC consultants, the American Academy of Pediatrics, and the United States' Surgeon General; and a "Black Box" warning in 1986 advising against administering aspirin to children and teenagers with chicken pox or flu symptoms without consulting a physician. 6,24,25,[27][28][29][30][31][32][33] The British Risk Factor Study found excess aspirin exposure in RS children and a 1986 advisory by the Committee on Safety of Medicines warned against administering aspirin to children under twelve. 34 Warning labeling on aspirin containing preparations was introduced, and modified in 2003 to warn against giving aspirin to children under sixteen without consulting a physician.…”
Section: Reye's Syndromementioning
confidence: 99%
“…Especially in the latter field, the case-control method has proven its potential. Examples include studies on aspirin use and Reye's syndrome [14], and, recently, betaagonists and fatal asthma 1151.…”
Section: Essentials Of the Case-control Studymentioning
confidence: 99%
“…A more controversial issue is the inclusion of several control groups in a case-control comparison. In a study on aspirin and Reye's syndrome, for example, 4 control groups were chosen [14]. In general, a clear understanding of the essentials of the study base will lead to sampling of one control group only.…”
Section: The Choice Of a Control Groupmentioning
confidence: 99%